Occupational differences in advance care planning: Are medical professionals more likely to plan?. (March 2021) - Carr, Deborah; Kalousova, Lucie; Lin, Katherine; Burgard, Sarah
Abstract: Advance care planning (ACP) helps ensure that treatment preferences are met at the end of life. Medical professionals typically are responsible for facilitating patients' ACP, and may be especially effective in doing so if they have first-hand insights from their own planning. However, no large-scale U.S. studies examine whether persons working on the front lines of health care are more likely than other workers to have done ACP. We contrast the use of three ACP components (living wills, durable power of attorney for health care, and informal discussions) among persons working in medical, legal, social/health support services, other professional, and other non-professional occupations. Data are from the Health and Retirement Study (n = 7668) and Wisconsin Longitudinal Study (n = 5464). Multivariable logistic regression analyses are adjusted for socioeconomic, demographic, health, and psychosocial factors that may confound associations between occupational group and ACP. Medical professionals in both samples are more likely than other professional workers to discuss their own treatment preferences, net of all controls. Medical professionals in the WLS are more likely to execute living wills and DPAHC designations, whereas legal professionals in the HRS are more likely to name a DPAHC. Non-professional workers are significantly less likely to do all three types of planning, although these differences are accounted for by socioeconomic factors. Social and health services professionals are no more likely than other professionals to do ACP. The on-the-job experiences and expertise of medical professionals may motivate them to discuss their own end-of-life preferences, which may render them more trustworthy sources of information for patients and clients. The Affordable Care Act provides reimbursement for medical professionals' end-of-life consultations with Medicare beneficiary patients, yet practitioners uncomfortable with such conversations may fail to initiate them. Programs to increase medical professionals' own ACP may have the secondary benefit of increasing ACP among their patients. Highlights: Medical professionals are most likely to do and discuss advance care planning (ACP). Non-professionals are least likely to do ACP, a pattern accounted for by education. Medical professionals' own ACP may make them trustworthy advisors to patients.